Posers, fakers, & wannabes : unmasking the real you - Manning, Brennan; Hancock, Jim, 1952- (Colorado Springs, CO : NavPress, 2003)
Provides insight into behaving as a child of God, knowing that He loves each person's true self, not the "poser" who pretends all is well even when life is spinning out of control.
Come out, come out, wherever you are -- The poser -- Who's your daddy? -- Abba's child -- Holier than God -- Resurrection -- Holy desire.
Includes bibliographical references.
Keywords: Teenagers -- Religious life; Teenagers -- Conduct of life; Christian life; Conduct of life; Self-acceptance.